2011
DOI: 10.1111/j.1365-2109.2011.02980.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyunsaturated fatty acids on the fecundity of the Amazon river prawnMacrobrachium amazonicum(Heller, 1862)

Abstract: Effects of the ratio of dietary fatty acids, namely n‐3 (mainly long chain polyunsaturated – LC‐PUFA) to n‐6 PUFA on the fecundity of Macrobrachium amazonicum were evaluated. In T1, the diet had equal and low levels of dietary n‐3 and n‐6 fatty acids (6 mg g−1). In T2, the concentration of n‐3 (6 mg g−1) was a half of the concentration of the n‐6 (12 mg g−1), and in T3, the diet had equal and high concentrations of n‐3 and n‐6 (12 mg g−1). Females with ovaries in stages I, III and V were collected. Higher gona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 26 publications
1
14
0
4
Order By: Relevance
“…The dietary treatments B1 and B2, containing 5.7–8.33% ARA and 21.78–22.49 % LOA of total fatty acid, led to higher reproductive performance of M. rosenbergii than treatments A1 and A2, containing 6.17–9.43% ARA and 14.85–13.35% LOA. Positive effects of dietary LOA levels on reproductive performance of broodstock and larval quality observed in this study were consistent with those observed by Cavalli, Lavens & Sorgeloos (1999) for M. rosenbergii and Ribeiro et al (2012) for M. amazonicum . Ribeiro et al (2012) found that the dietary treatment with approximately 12 mg g −1 DW LOA could improve fecundity of mature female M. amazonicum .…”
Section: Discussionsupporting
confidence: 91%
“…The dietary treatments B1 and B2, containing 5.7–8.33% ARA and 21.78–22.49 % LOA of total fatty acid, led to higher reproductive performance of M. rosenbergii than treatments A1 and A2, containing 6.17–9.43% ARA and 14.85–13.35% LOA. Positive effects of dietary LOA levels on reproductive performance of broodstock and larval quality observed in this study were consistent with those observed by Cavalli, Lavens & Sorgeloos (1999) for M. rosenbergii and Ribeiro et al (2012) for M. amazonicum . Ribeiro et al (2012) found that the dietary treatment with approximately 12 mg g −1 DW LOA could improve fecundity of mature female M. amazonicum .…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, our data indicates that female size can also limit fertility in M. amazonicum populations, since females from Pará are larger than those from Mato Grosso do Sul and produced a higher number of eggs. The fecundity of M. amazonicum varies widely, reaching more than 7,200 eggs per clutch (Ribeiro et al, 2012). However, other studies have reported much lower values (Coelho et al, 1982: fecundity = 6,000 eggs; Silva et al, 2004: maximum fecundity = 2,193 eggs; Lobão et al, 1986: fecundity = 1,344 eggs; Gamba, 1984: fecundity = 1,000 eggs; Scaico, 1992: mean fecundity = 595 eggs).…”
Section: Discussionmentioning
confidence: 95%
“…For example, Lobão et al (1986) reported for other species of the same genus such as Macrobrachium potiuna, M. iheringi (Ortmann, 1898), M. australiense (Holthuis, 1950), M. borellii (Nobili, 1896) and M. jelskii (Miers, 1877) absolute fecundities lower than 200 eggs. Although M. amazonicum has a relatively high fecundity, with a production of 6,000 to 7,000 eggs in aquaculture tanks (Ribeiro et al, 2012), this is considered low compared to species of greater commercial interest and that reach larger sizes, such as M. rosenbergii (De Man, 1879), M. acanthurus (Wiegmann, 1836), M. carcinus (Linnaeus, 1758) and M. malcolmsonii (H. Milne-Edwards) (Coelho et al, 1982;Valenti, 1984;Lobão et al, 1985;Scaico, 1992). According to Ismael & New (2000), M. rosenbergi, which is the most used species for aquaculture in Brazil, and M. carcinus, present fecundity ranging from 80,000 to 100.000 eggs per female.…”
Section: Discussionmentioning
confidence: 99%